2007
DOI: 10.1136/emj.2007.046714
|View full text |Cite
|
Sign up to set email alerts
|

Propofol for procedural sedation in the emergency department

Abstract: Propofol is effective and safe for procedural sedation in the ED. Propofol has a considerably shorter duration of action than midazolam, thereby shortening the period of sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Similarly, in an observational study by Dunn et al 12 of 48 non-fasting patients using Propofol, no patient developed pulmonary aspiration. A Cochrane review of 38 randomised controlled trials did not show an increased risk of pulmonary aspiration with shorter fluid fast 13…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, in an observational study by Dunn et al 12 of 48 non-fasting patients using Propofol, no patient developed pulmonary aspiration. A Cochrane review of 38 randomised controlled trials did not show an increased risk of pulmonary aspiration with shorter fluid fast 13…”
Section: Discussionmentioning
confidence: 78%
“…Cheol et al ,10 who conducted a randomised double blind comparative study using propofol alone and combined propofol and midazolam in colonoscopy, found that both propofol alone and combined propofol and midazolam are safe and effective. A combination of propofol and midazolam on the other hand is judged more effective than using propofol alone in producing sedation without significant adverse effects 11 12…”
Section: Discussionmentioning
confidence: 99%
“…Accident and emergency (A&Es) departments continue to draw inferences of 'safety' after describing sedation with propofol in limited numbers (without reference to 95% CI) and with little emphasis on maintaining verbal contact [16,17]. The Academy of Royal Colleges document on safe sedation practice, led by the Royal College of Anaesthetists but with members from all relevant specialties including the Faculty of Accident & Emergency Medicine, is very clear on this topic.…”
Section: Discussionmentioning
confidence: 99%